Pengembangan Model Komunikasi Pariwisata Berbasis Kearifan Lokal di Kawasan Kampung Ulos Hutaraja - siahaan, uliasi patricia; Harris, Abdul (Universitas Medan Area, 2025)
Ulos Hutaraja Village has great potential as a tourist destination based on the local wisdom of the Batak people. However, its management faces communication challenges that cause tourists to lack understanding of the cultural values conveyed. This study aims to analyze the development of a tourism communication model based on local wisdom in the Ulos Hutaraja Village Area. This study uses a qualitative exploratory method with in-depth interview techniques, participatory observation, and documentation studies. The analysis was carried out with a thematic approach and data triangulation to increase the validity of the findings. The results of the study show that tourism communication in Ulos Hutaraja Village is carried out through interpersonal communication, group communication, and digital communication. Interpersonal communication allows for direct interaction between tourists and ulos artisans, while group communication becomes a means of stakeholder coordination. Digital communication is used for promotion and education, but it still faces technological gaps and limited access for local communities. Other obstacles include limitations in the delivery of cultural narratives and differences in interests between parties. Therefore, a more effective communication model is needed to increase community involvement and maintain the preservation of Batak culture in tourism.